PENGARUH LATIHAN LADDER DRILL TERHADAP KECEPATAN DRIBBLING PEMAIN FUTSAL SDN NGAGLIK 01 KOTA BATU - Bintang Ega Putra Syandana; Imam Hariadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study focuses on assessing the extent to which ladder drill training can affect dribbling speed at SDN Ngaglik 01 Batu City. The study design uses quantitative research with an experimental (pre-experimental) approach, namely through the concept of the one group pretest-posttest design. The main subjects through this research involved members of the SDN Ngaglik 01 Batu futsal team, extracurricular students in grades IV to VI. A sample of 30 was taken using a training method with a flat ladder. The strategy for obtaining data utilizes a testing method, with the measurement of dribbling speed in this study using a test developed by Mielke (2007). By processing the data through normal distribution testing, variance equality testing, and paired sample T-test. The output of this study can be observed that the average value recorded in the posttest (13.63) has increased compared to the pretest (14.76), and can also be seen from the p-value in the paired t-test showing a value of 0.000 which means the results of this study have a significant influence. Based on these findings, it shows that dribbling speed training with ladder drills has a big influence on increasing the dribbling speed of futsal players at SDN Ngaglik 01 Batu City.